Telaah Sarana dan Prasarana Pendukung Taman Wilhelmina Kota Pangkalpinang - Tiara Millenia Loziska; Sabrina Alifia Zahra (Universitas Muhammadiyah Palembang, 2024)
As one of the Green Open Spaces (RTH) in Pangkalpinang City, Wilhelmina City Park serves an important function for the community. This research aims to identify and measure the completeness and quality of facilities and infrastructure in Wilhelmina City Park, focusing on fulfilling the functions of a city park. Efforts to develop the park are made to support the concept of a livable city. A qualitative descriptive approach is used in this research, with site analysis as the main method covering aspects of park functions such as social, ecological, hydrological, health, and aesthetic functions. This research is important because Wilhelmina City Park is one of the vital public assets in improving the quality of life for city residents. By analyzing the completeness of facilities and infrastructure in Wilhelmina City Park, this research can provide a better understanding of how well the park meets the needs of the community in terms of recreation, sports, and relaxation. The results show that the park has provided adequate facilities and infrastructure, with good quality, thus, overall, Wilhelmina City Park is effective in fulfilling various functions as a city park, including social, ecological, hydrological, health, and aesthetic functions.